Peer assessment platform of clinical skills in undergraduate medical education - Chen, Liling (J Int Med Res, 2019)
OBJECTIVE: The study objective was to enhance clinical skills among undergraduate students majoring in clinical medicine in performing physical examination by establishing a novel platform for peer assessment of clinical skills. METHODS: A total 126 Year 2012 students majoring in medicine and receiving traditional training were assigned to the control group, and 126 Year 2013 students receiving instruction via the peer assessment platform of clinical skills were allocated to the study group. Scores of the physical examination, paper exam, and peer assessment were compared using a t-test, and we performed linear correlation analysis of the data. RESULTS: Scores of the physical examination and peer assessment among Year 2013 students (the study group) were significantly higher than those in the control group. Paper exam scores in the study group were also significantly higher than those in the controls. The three assessment scores did not differ significantly according to sex. CONCLUSIONS: The peer assessment platform can not only improve medical students’ skills and capabilities in physical examination, it can also enhance their theoretical knowledge of basic clinical principles. We determined that sex was not related to the assessment scores obtained by medical students.